Index Card Match Model for Improving Mathematics Learning Outcomes: Model Kartu Indeks untuk Meningkatkan Hasil Pembelajaran Matematika - Ike Opiyani; Nurlev Avana; Apdoludin Apdoludin (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Student motivation and learning outcomes in mathematics at the elementary level remain a persistent challenge. Specific Background: At SDN 05/II Air Gemuruh, Grade IV students demonstrated low engagement and achievement in mathematical sentences and calculations due to monotonous, teacher-centered instruction. Knowledge Gap: Few studies have systematically examined interactive strategies such as the Index Card Match model in improving both the learning process and outcomes in mathematics. Aims: This study aimed to enhance mathematics learning motivation and achievement by implementing the Index Card Match model through Classroom Action Research (CAR). Results: Conducted in two cycles with 20 students, findings revealed significant improvements in teaching quality, student engagement, and mastery. Teacher performance scores rose from 61.11% to 88.89%, the number of students in the “very good” category increased from 20% to 45%, and mastery learning outcomes improved from 55% to 80%. Novelty: This research provides empirical evidence of the Index Card Match model’s effectiveness in fostering active participation and sustained motivation in mathematics learning. Implications: The findings suggest that integrating interactive models can transform learning environments, making mathematics more engaging and effective for primary school students. Highlights: Improved teacher performance and student engagement. Significant increase in mastery of mathematics. Index Card Match proven effective in primary education. Keywords: Index Card Match, Mathematics Learning, Student Motivation, Classroom Action Research, Learning Outcomes